2013
DOI: 10.1017/s0007123413000410
|View full text |Cite
|
Sign up to set email alerts
|

Easing the Heavy Hand: Humanitarian Concern, Empathy, and Opinion on Immigration

Abstract: The bulk of the public opinion research on immigration identifies the factors leading to opposition to immigration. In contrast, we focus on a previously unexplored factor yielding support for immigration: humanitarianism. Relying upon secondary analysis of national public opinion survey data and an original survey experiment, we demonstrate that humanitarian concern significantly decreases support for restrictive immigration policy. Results from our survey experiment demonstrate that in an information environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 54 publications
5
61
0
Order By: Relevance
“…Montada and Schneider (1989), for example, found that Germans who empathize with immigrants tend to support prosocial activities. Further, in three studies conducted in the U.S.A., it was found that individual differences in humanitarian concern and empathy were associated with support for immigration (Newman et al 2015; see also Bansak, Hainmueller, and Hangartner 2016). Iyer, Leach, and Crosb (2003) found that empathy is a general predictor of support for different affirmative action policies for African Americans.…”
Section: Empathy and Angermentioning
confidence: 99%
“…Montada and Schneider (1989), for example, found that Germans who empathize with immigrants tend to support prosocial activities. Further, in three studies conducted in the U.S.A., it was found that individual differences in humanitarian concern and empathy were associated with support for immigration (Newman et al 2015; see also Bansak, Hainmueller, and Hangartner 2016). Iyer, Leach, and Crosb (2003) found that empathy is a general predictor of support for different affirmative action policies for African Americans.…”
Section: Empathy and Angermentioning
confidence: 99%
“…Second, cognitive‐developmental theories hold that the effectiveness of social input from parents and peers might depend on the child's socio‐cognitive mindset (Aboud & Amato, ; Black‐Gutman & Hickson, ; Levy, ). Research has shown empathy to moderate the effects of humanitarian concern inductions on immigrant policies (Newman, Hartman, Lown, & Feldman, ) and the effects of ingroup norms on outgroup liking (Nesdale, Griffiths, Durkin, & Maass, ). In line with this reasoning, the attitudes of highly empathic adolescents might be less affected by their parents or peers’ prejudice.…”
Section: Introductionmentioning
confidence: 99%
“…It has been convincingly argued that both cognitive and affective aspects of empathy are essential elements for democratic deliberation (e.g., Newman et al 2015). Moreover, deliberation about immigration can be expected to raise concerns regarding the perspectives of the relevant outgroup (i.e., immigrants).…”
Section: Discussionmentioning
confidence: 99%